The development of economic sanctions in the practice of the United Nations Security Council - Murphy, Rosemary Alice (2011)
The United Nations was established in the belief that working together states could curb the use of force and the damage to states and individuals associated with it. Upon its creation the United Nations Security Council became the global policeman enforcing the rules of the Charter aided by the weapons contained in Chapter V11. One of those weapons was the recourse to economic sanctions. In theory, if the economic lifeblood of a state is cut off it will be forced to modify its behaviour without the need for military intervention. As such, economic sanctions are an attractive resource for an institution seeking to avoid recourse to the use of force. In practice, however, economic sanctions have proven to be a complex tool, which have caused significant damage to those targeted by them. They have caused significant humanitarian difficulties, have been widely breached and have, in some instances, only served as a prelude to the use of force. Literature in this field to date has concentrated on single sanctions regimes or particular aspects of sanctions. It has, therefore, failed to get to the heart of the issue, which is: what has caused these problems, are they being appropriately addressed and how should they be resolved going forward. This thesis focuses on these issues. By tracing the development of economic sanctions from the establishment of the United Nations to date it offers a unique perspective on how they have evolved. It uses case studies and illustrative examples supported by a wide range of legal, political, historical and economic material to show the context in which economic sanctions are taken. It also critically analyses the difficulties that have arisen with sanctions regimes and the attempts that have been made to resolve them. Aligned to the consideration of economic sanctions is a reflection on the extent to which the power of the United Nations Security Council has developed during this time period. It suggests that the United Nations use of economic sanctions, in light of recent judicial decisions, is under threat and offers a solution in the form of a proposal for two new institutions, which would support the United Nations in its use of economic sanctions.